The prevalence and correlates of tobacco use among 7-9th grade students in Bangladesh. (September 2019) - Khan, Jahidur Rahman; Raheem, Enayetur; Daniel, Mark
Abstract: Rising tobacco use (TU) among youth aged 15–24 is a public health concern globally, especially in developing countries. This study examined the correlates of ever and current TU among 7-9th grade students in Bangladesh, accounting for school- and grade-level variations. A complete case analysis was performed of 3150 students in grades 7–9 (age range 11–17 years) from the 50 schools surveyed in the 2013 Bangladesh Global Youth Tobacco Survey (GYTS). Factors associated with TU were analysed using multilevel logistic regression. The prevalence of ever TU (ETU) and current TU (CTU) was 19% and 7%, respectively. TU was associated with higher age, male gender, and receipt of >50 Bangladeshi Taka (BDT) per week as pocket money. TU was also statistically significantly associated with seeing others smoking at home (ETU: adjusted odds ratio [AOR] = 2.47; 95% confidence interval [CI] = 2.01 to 3.06 and CTU: AOR = 2.43; 95% CI = 1.74 to 3.38) or other places (ETU: AOR = 1.62; 95% CI = 1.26 to 2.10 and CTU: AOR = 2.96; 95% CI = 1.81 to 4.84), and receipt of tobacco products from friends (ETU: AOR = 1.70; 95% CI = 1.06 to 2.74; and CTU: AOR = 3.72; 95% CI = 2.11 to 6.56). Students who supported banning smoking in public places and who believed "smoke from others' tobacco use is harmful" had lower odds of being CTU. Substantial school-to-school and grade-to-grade variation were observed in TU among students. Grades 7–9 students' TU is related to age and exposures indicative of tobacco-related social and normative influences in Bangladesh. As a public health priority, TU among grades 7–9 students requires the implementation of integrated social-ecological intervention strategies targeting both behaviour and the environmental contexts that shape behaviour. Highlights: The prevalence of tobacco use among grade 7–9 students is high in Bangladesh. Tobacco use among student is related to age and exposures indicating tobacco-related social and normative influences. The implementation of an integrated social-ecological intervention strategy is essential to reduce tobacco use.